Microbial population selection in integrated fixed-film sequencing batch reactors operated with different lengths of oxic and anoxic conditions. Issue 5 (19th March 2021) - Aqeel, Hussain; Basuvaraj, Mahendran; Liss, Steven N.
Abstract : BNR granules rich in amyloid adhesins and denitrifying bacteria were formed in the SBRs that were operated with extended anoxic conditions. Abstract : The paper assesses the impact of the duration of oxic and anoxic conditions on the selection of microbial populations in laboratory-scale integrated fixed-film sequencing batch reactors (IF-SBRs). IF-SBRs were fed anaerobically with glucose and sodium acetate based synthetic wastewater. Three IF-SBRs were operated with different lengths of oxic and anoxic periods, and a control IF-SBR was operated with continuous aeration during the react phase of the SBR cycle. Compact flocs were formed in the control bioreactor, whereas granular sludge developed rapidly within ten days in the IF-SBR operated with an extended anoxic phase (3.25 hours within the six-hour cycle). Filamentous bulking was observed in the IF-SBRs that were operated with relatively moderate anoxic periods. Confocal laser scanning microscopy of the granular sludge revealed that β-polysaccharide and amyloid adhesins were predominant in the periphery and core of the granules, respectively. 16S rRNA gene sequencing (Illumina MiSeq) revealed rapid selection and increases in the relative abundance of Flavobacterium, Caulobacter, Dechloromonas, Zoogloea, and bacterial genera related to the family Comamonadaceae, that were predominant in the granular sludge. The functional capabilities of the bacteria that were predominant in the granular sludge include quorum sensing, formation of storage polymers, and denitrification. Optimizing the length of oxic and anoxic conditions in sequencing batch reactors, and in the configuration in this study which was a hybrid system consisting of flocs, biofilm and granular sludge, is an important consideration in the selection of bacterial populations important to the development of microbial structures, and granular sludge in particular.